Pengendalian Stunting Melalui Edukasi Pengolahan Ragam Makanan Sehat dari Bahan Lokal dan Pendampingan Posyandu di Kelurahan Bongsari, Kota Semarang (Kolaborasi UNNES - PT Phapros, Tbk): Stunting Preventin through A Training on Processing a Variety of Healthy Foods from Local Ingredients and Assistance for Posyandu Cadres in Kelurahan Bongsari, Semarang City (Collaboration of UNNES and PT Phapros, Tbk) - Kusumaningtyas, Ratna Dewi; Lestari, Yanesti Nuravianda; Handayani, Prima Astuti; Laila, Rachma Akmila; Salsabila, Anida; Rahmah, Aisyah Khalimatur; Putri, Silvia Nouvelia; Rachmadi, Moch Faizal; Jannah, Reni Ainun; Imani, Nadya Alfa Cahaya; Barita, Asyera Dewi; Kun, Stefania Orance; Nindita, Ariana Eka (Universitas Mataram, 2024)
Stunting is among the national priority issue in the National Medium Term Development Plan (RPJMN). At the global level, stunting is also a priority based on the Sustainable Development Goals (SDGs), especially related to the 3rd and 2nd SDGs, namely